A Comparative Study of Cervical Length Measurement by Ultrasound Versus Digital Examination for Predicting Preterm Labor in Low-Risk Population - Mankani, Lata K; S Ankalagi, Santosh (Journal of Neonatal Surgery, 2025)
Background: Preterm birth remains a significant cause of neonatal morbidity and mortality worldwide. Early identification of women at risk for preterm labor is crucial for timely intervention. This study aimed to compare the accuracy of cervical length measurement by transvaginal ultrasound versus digital examination in predicting preterm labor in a low-risk population. Methods: This prospective cohort study included 240 pregnant women with singleton pregnancies between 20-24 weeks of gestation without prior history of preterm birth. Cervical length was assessed by both transvaginal ultrasound and digital examination at enrollment and at 28 weeks. Participants were followed until delivery, with preterm birth (delivery before 37 completed weeks) as the primary outcome. Sensitivity, specificity, positive and negative predictive values were calculated for both methods. Receiver operating characteristic (ROC) curves were constructed to determine optimal cut-off values. Results: The overall preterm birth rate was 8.75% (21/240). The mean cervical length by ultrasound was significantly shorter in women who delivered preterm compared to those who delivered at term (28.3±4.2 mm vs. 36.5±3.9 mm, p<0.001). Digital examination had lower accuracy in estimating cervical length compared to ultrasound (r=0.42, p<0.001). For prediction of preterm birth, a cervical length <30 mm by ultrasound at 20-24 weeks had a sensitivity of 76.2%, specificity of 82.4%, positive predictive value of 29.1%, and negative predictive value of 97.3%. In contrast, digital examination had a sensitivity of 38.1%, specificity of 68.4%, positive predictive value of 10.4%, and negative predictive value of 92.1%. Conclusion: Transvaginal ultrasound measurement of cervical length is superior to digital examination for predicting preterm labor in low-risk women. A cervical length <30 mm at 20-24 weeks gestation can effectively identify women at risk for preterm birth, allowing for closer surveillance and timely interventions.